Risk Factors for Maternal and Fetal Outcome in Placenta Accrete Spectrum Associated with Placenta Previa in Libya - Naamat Abid; Laila Benhamida; Maha Alzergany; Mona Bin Salah; Salma Almeslati (Khalij-Libya Journal of Dental and Medical Research, 2023)
Background and aims. Placenta accreta spectrum (PAS) is a pathologic invasion of the placental trophoblasts to the myometrium and beyond and is associated with severe maternal morbidity. This study was aimed to determine the risk factors and maternal and fetal outcome of cases with PAS associated with placenta previa in Libyan Maternity Hospital. Methods. We performed a cross section study of pregnant women with PAS associated with placenta previa at department of Obstetrics and Gynecology in Aljala Maternity Hospital in Tripoli, Libya during the period of 2021. In these cases, the earlier diagnosis was recognized by an ultrasonographic. The study included 143 pregnant women with PAS associated with placenta previa. Data were collected by specific and validated questionnaires. All pregnant women diagnosed with placenta accrete whose age ranged between ≥ 18 years were included. Women with others diseases were excluded from the study. Results. A total 143 pregnant women diagnosed with placenta accreta whose age ranged between 18 to 45 years (mean age group was 33.56 ± 5.8 years). All the pregnant women had risk fac¬tors for abnormally invasive placenta such as previous placenta previa, cesarean delivery, parity and repeat miscarriage. 63.0% of women were delivered by emergency cesarean section, mean of gestational age was 34.07 weeks. In the management of bleeding, 70.6% were received blood transfusion, 15.4% were treated by hysterectomy and 84.6% were received conservative treatment, such as bilateral uterine artery ligation, balloon tamponade. Internal hypogastric artery ligation and avoiding of bleeding and infection. 60.1% were admitted in the medical intensive care units for deterioration of their health condition with a mean duration stay at ICU of 4.45 ± 4.5 day with no death reported between them. Regarding fetal outcome, preterm delivery was 55.2% from 33 - 34 weeks and the mean birth weight was 2.57 ± 0.55 gm, NICU admission was 50 (35.0%). There is 10 neonatal death reported (6.9%). Conclusion. PAS is a harmful event in Libyan women’s pregnancy and leads to a high maternal morbidity with adverse neonatal outcomes. The critical risk indicators for PAS are women age, previous LSCS, placenta previa, parity, repeat miscarriage. Thus, early recognition of the risk factors and planned management improve maternal and fetal outcomes in Libya.